Optimising environmental watering of floodplain wetlands for fish. (30th June 2014) - Beesley, Leah; King, Alison J.; Gawne, Ben; Koehn, John D.; Price, Amina; Nielsen, Daryl; Amtstaetter, Frank; Meredith, Shaun N.
Summary Flow alteration has reduced connectivity between many of the world's rivers and their floodplains, causing changes in riverine productivity and the isolation of floodplain wetlands. Environmental water is being increasingly used to help restore wetland habitats and their biota, including fish. However, some of these managed deliveries of water occur into discrete wetlands via artificial structures or at unseasonal times and may not deliver the expected gains in fish production. In the Murray River, south‐eastern Australia, we examined the relationship between attributes of watering and fish production (species‐specific recruitment, total abundance), at two time intervals: short term (6–8 weeks after watering) and at the end of the spawning season (April) for 26 discrete watering events. The study also recognised the importance of habitat in mediating fish responses to watering and examined whether fish abundance after environmental water delivery is better predicted by attributes of watering or wetland characteristics? We found that attributes of watering, including water source, its method of delivery and timing, best described fish recruitment (0+ abundance) and total fish abundance. Managers of environmental water may be able to optimise fish recruitment and abundance if they source their water from the river and deliver it during the spawning period of the target species via means that facilitate fish passage.